Perception of Urban Habitat and the Structure of Human Interaction. Dialogues with the Artist as Part of Creative Intervention - Breska, Katarzyna (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
In this paper I bring closer some of the aspects of my work, I show the approach to the space when working in public locations. The components of this approach are a careful observation of the environment, spending time with the locals, talking to them, taking into account the symbolic nature of the contents brought by the people. So I quote and comment some of the dialogues that happened between me and the passers by during a four week creative intervention in the city’s oldest street.